The Reflection of Mothers in Judith Balassa’s Correspondence in the Second Half of the 17th Century (Theatrum historiae, 2024)
The early modern society, usually considered to be patriarchal, determined precise roles for women, who were defined by requirements based mainly on their position in the private sphere. In their family, they assumed the roles of daughters, sisters, mothers, wives, widows, grandmothers, etc. This paper focuses on the role of the mother in early modern society by analysing the correspondence of the Koháry family. For this purpose, the epistolar communication between Judith Balassa (c. 1630–c. 1685), the widow of Stephen I. Koháry (1616–1664), and her eldest son Stephen II. Koháry (1649–1731) has been studied. The correspondence was written during two important periods in the life of the Koháry family. The first was during the studies of Stephen II. Koháry in Vienna after the death of his father in 1664, followed by his accession to the post of the captain-general of Fiľakovo, which he held until his capture by Imrich Thökoly in September 1682. The paper examines the manifestations of maternal care and the understanding of this role, as derived from the correspondence between mother and son, in the context of their early modern¨ conception.
Keywords: Mother; Motherhood; Care; Correspondence; Early Modern Period